2021
DOI: 10.1177/08862605211055149
|View full text |Cite
|
Sign up to set email alerts
|

Can Emerging Adults’ Dating Psychological Aggression be Explained by Family-of-Origin Psychological Aggression, Emotion Dysregulation, and Drinking?

Abstract: Intimate partner violence (IPV) impacts the lives of millions of individuals; nearly 1 in 4 women and 1 in 7 men report experiencing IPV during their lifetime. Previous studies frequently cite family-of-origin aggression as a risk factor for later experiences with IPV. Research with adults who engage in IPV finds an association with childhood exposure to family violence, but the strength of that association may vary. Psychological aggression often pre-dates more severe IPV and college students are a particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 86 publications
0
1
0
Order By: Relevance
“…As highlighted by the researchers, in addition, parental knowledge (i.e., knowledge of the child's friends, whereabouts and activities) as measured by the nine-item parenting questionnaire (Alabama Parenting Questionnaire 9 -APQ-9) protected the subjects from progression from experimental to problematic alcohol use [35]. Correlations between emotional dysregulation and drinking behaviour have also been observed in other populations, including 9/11 New York Two Towers survivors [36], perpetrators of relationship violence [37] and HIV-infected individuals [38]. It has also been observed that difficulties in emotion regulation and goal focus may contribute to higher rates of alcohol use during the COVID-19 pandemic [39].…”
Section: Emotion Regulation Disorders and Alcohol Drinking In Clinica...mentioning
confidence: 87%
See 1 more Smart Citation
“…As highlighted by the researchers, in addition, parental knowledge (i.e., knowledge of the child's friends, whereabouts and activities) as measured by the nine-item parenting questionnaire (Alabama Parenting Questionnaire 9 -APQ-9) protected the subjects from progression from experimental to problematic alcohol use [35]. Correlations between emotional dysregulation and drinking behaviour have also been observed in other populations, including 9/11 New York Two Towers survivors [36], perpetrators of relationship violence [37] and HIV-infected individuals [38]. It has also been observed that difficulties in emotion regulation and goal focus may contribute to higher rates of alcohol use during the COVID-19 pandemic [39].…”
Section: Emotion Regulation Disorders and Alcohol Drinking In Clinica...mentioning
confidence: 87%
“…Korelację pomiędzy dysregulacją emocjonalną a zachowaniami związanymi z piciem alkoholu obserwowano także w innych populacjach, m.in. u osób, które przeżyły atak na nowojorskie wieże z 11 września 2001 r. [36], sprawców przemocy w relacjach partnerskich [37] czy osób zarażonych HIV [38]. Obserwowano również, że trudności w regulacji emocji i w koncentrowaniu się na celu mogły przyczyniać się do częstszego sięgania po alkohol podczas pandemii COVID-19 [39].…”
Section: Emotion Regulation Disorders and Alcohol Drinking In Clinica...unclassified
“…Based on physiological and neural indicators of emotion regulation, the DERS total score represents a reliable global index of overall ED (Gratz et al, 2006;John and Eng, 2014). The DERS demonstrates high internal consistency with Cronbach's alpha ranging from 0.77 to 0.93 (Gratz and Roemer, 2004;Dhruve and Oliveros, 2022). Conversely, discriminant validity evidence for the DERS subscales is limited (John and Eng, 2014).…”
Section: Methodsmentioning
confidence: 99%